A Concept Analysis of Self‐Care Based on Islamic Sources. Issue 3 (1st December 2015) - Marzband, Rahmatollah; Zakavi, Ali Asghar
Abstract : Purpose: This article describes the concept of self‐care from Islamic texts. Method: Rodgers' evolutionary model of concept analysis was used in this study. Findings: Self‐care is a series of responsible activities to God for health promotion, preventive disease and remedy. It encompasses physical, mental, spiritual, and social dimensions. Conclusion: A comprehensive definition of the concept of self‐care ensued from a review of Islamic literature. Implications for Nursing Practice: Since the nurses instruct and assist individuals as they engage in self‐care, using a comprehensive definition of self‐care based on Islamic sources would provide an anchor linking for them as they interact with Muslim patients.